Cognitive performance in transient global hypoxic brain injury due to moderate drowning. Issue 5 (28th May 2018) - Nucci, Mariana Penteado; Lukasova, Katerina; Vieira, Gilson; Sato, João Ricardo; Amaro Júnior, Edson
ABSTRACT: Introduction : Drowning is a serious and frequently neglected public health threat. Primary respiratory impairment after submersion often leads to brain dysfunction. Depending on the period of global hypoxia (respiratory failure), clinical aspects of neurological dysfunction are evident on the first evaluation after the water rescue. Nowadays, many neuropsychological assessments after drowning are inconclusive, with some studies reporting only minor neurological or cognitive impairments. The aim of this study is to identify measures in neuropsychological tests that most contribute to classify volunteers as moderate drowning subjects or healthy controls. To the best of our knowledge, this study is the first neuropsychological prospective case-control study of moderate drowning in a country with large coastal cities. Method : Fifteen moderate drowning patients (DP), who met the inclusion criteria, were compared with 18 healthy controls (HC). All subjects were assessed on memory, learning, visual spatial ability, executive function, attention, and general intellectual functioning and underwent structural magnetic resonance (MR) imaging of the brain at 3.0 T, in order to exclude subjects with anatomic abnormalities. Results : Neuropsychological tests assessing learning, execution function, and verbal fluency—Rey Auditory Verbal Learning Test (RAVLT) general learning ability, Digit Span total, Phonological Verbal Fluency (total FAS correct), and Brief Visuospatial Memory Test Revised (BVMT) correct recognition—have the strongest discriminating ability, using predictive models via the partial least squares (PLS) approach for data classification, while the other tests have shown similar predictive values between groups. Conclusions : Learning, execution function, and verbal fluency domains were the most critically affected domains. Serious impairments in the same domains have already been reported in severe drowning cases, and we hypothesize that subtle alterations found in moderate drowning cases, although not sufficient to be detected in daily routine, may possibly have a negative impact on cognitive reserve.